Case Study : Seri Pena Enterprise / Nur Humaira Suhaimi - Suhaimi, Nur Humaira (2020)
Seri Pena Enterprise is located at Bachok, Kelantan. This small company started their business in 2008, for about 12 years they have been involved in this local food industry. The company does not have a specific organizational structure since it is a small company. It has three general managers named Mohd Asri bin Abdul Rahman, Mat Hasan and Nik Rozaidi. It also has about seven foreign-born employees. The product produced by this company is budu branded as Cap Dua Ikan Mas and their motto is Sedap Sengoti which means so delicious in their native accent. They produced twi different types of budu which are “budu merah” and “budu kampung”. Budu is traditionally made by mixing anchovies and salt in its own ratio, thus the process of making budu solely depend on the condition of the raw material. The raw material usually found once a year in the months of August to September during the monsoon season and it is uncertain. This company get their raw material from Kelantan, Terengganu and even imported from Thailand